Anesthetic considerations for labor and delivery in women with cerebrospinal fluid shunts. (May 2017) - Rajagopalan, S.; Gopinath, S.; Trinh, V.T.; Chandrasekhar, S.
Highlights: The incidence of CSF shunt failure is high during pregnancy. Neuraxial anesthesia can be safely performed in women with functional shunts. In women with shunt malfunction, general anesthesia is preferred for cesarean delivery. Abstract: Background: The anesthetic management of labor and delivery in pregnant women with cerebrospinal fluid shunts can be challenging. We conducted a literature review to understand the anesthetic implications in pregnant women with cerebrospinal fluid shunts. Methods: We searched PubMed, EMBASE, and Medline databases to identify reports of pregnant women with cerebrospinal fluid shunts during the 30-year period from 1985 to 2015. Twenty-four studies reporting anesthetic techniques for labor and delivery were included in the analyses. Results: A total of 97 women with 130 pregnancies were included. Ventriculo-peritoneal shunts (77%) were the most common type of shunt. Twenty-eight (29%) women had shunt malfunction during pregnancy, with 20 (71%) requiring shunt revision. Overall, 73 women (56%) delivered vaginally and 23 (40%) received epidural analgesia. Fifty-seven women (44%) underwent cesarean delivery and general anesthesia was used in 45% of cases. Conclusion: This review suggests that shunt malfunctions occurred commonly during pregnancy. The presence of neurological symptoms warrants careful evaluation of shunt function. Anesthetic management for labor and delivery varied and was dependent on shunt function. Epidural analgesia appears to be safe in women with functional shunts.